ANALISIS KUAT TEKAN BETON MENGGUNAKAN LIMBAH BOTOL KACA SEBAGAI PENGGANTI SENAGIAN AGREGAT HALUS DAN GULA MERAH SEBAGAI BAHAN TAMBAH / ADITIF BETON - Achmad Pahrul Rodji; Sahat Martua Sihombing; Novrihan Tanjung (Jurnal Sipil Krisna, 2022)
Various studies in the field of concrete were carried out in an effort to improve the quality of concrete, thetechnology of the research and experiment materials intended to answer the increasingly high demands on the useof concrete.One way to reduce excessive mining of natural materials is by utilizing waste glass bottles and brown sugar,especially glass bottles which area lot of waste and accumulate in the environment around the house.This study aims to analyze the compressive strength of concrete using wasteglass bottles and brown sugar as a substitute for fine aggregate and water. Mix Design in glass bottles and brownsugar as a substitute for fine aggregate and water. Mix Design in This study uses the SNI 2000 method. Thecomposition of glass bottle waste is 5% and 10% to fine aggregate while brown sugar is 0.25% and 0.50% againstwater. The specimens were cylindrical in shape with a diameter of 15 cm and a height of 30 cm as many as 24specimens aged 7, 14 and 28 days. The results of the average compressive strength using glass bottle waste and brown sugar with a composition of 5% and 10% for fine aggregate and 0.25% and 0.50% for water, namely for variation 1 of 8.98Mpa, 11.74 Mpa , 16.06 Mpa while for variation 2 it is 7.45 Mpa, 9.87 Mpa, 14.99 Mpa. then the percentagereduction of concrete variations 1 and 2 against normal concrete is 4.02%, 5.86%, 3.94% and 5.55%, 7.73%,5.01%.